POLICY ANALYSIS OF FOREIGN DENTENCES AT IMMIGRATION CHECKPOINT: THE DILEMMA OF RESPONSIBILITY BETWEEN IMMIGRATION AND AIRLINES - Rafsanjani Is Ma’rus; Fachrizza Sidi Pratama; Hana Farah Dhiba (Polteknik Imigrasi, 2022)
In Annex 9 of ICAO, airlines as passenger facilitators have obligations and responsibilities to pre-flight, flight, and after-flight passengers. The after-flight obligation of the airline also includes the consequences for the passenger if immigration is refused in the destination country. During a temporary detention, the airline must pay attention to and take care of the passenger's needs. The immigration detention room at the TPI is a place used by the immigration authorities as a place of detention because it still requires further supervision and investigation of the foreigner.After the immigration authorities have completed the detention, at the first opportunity the foreigner is placed on the transportation means (airplane) that carries him and becomes the responsibility of the person in charge of the transportation means (the airline) and all costs incurred are borne by the person in charge of the transportation means. This study uses a descriptive qualitative method with a normative juridical approach. The normative juridical approach is a research that begins deductively with an analysis of the provisions in the laws and regulations governing problems related to the implementation and analysis of the detention policy of foreigners at immigration checkpoints. It is hoped that this responsibility dilemma can be resolved with the existence of a legal basis in the form of regulations and SOPs related to the detention of foreigners at the TPI. In order to avoid overlapping authority in terms of fulfilling the rights of foreigners by the airline in the immigration area.